Effect of copper loading on TiO2 photocatalyst for Photodegration of Polybrominated Diphenyl Ether (PBDEs) - Norsahida Azri; Rusmidah Ali; Wan Azelee Wan Abu Bakar (Pusat e-pembelajaran, UMS, 2023)
Stockholm Convention has classified the polybrominated diphenyl ethers (PBDEs) as persistent toxic organic pollutants (POPs) are used widely as flame retardant in daily domestic products. Due to its high ecological risk, high toxicity, persistent, and bioaccumulation potential to both humans and wildlife, this present paper aims to study the photodegradation of PBDEs under UV light using Cu/TiO2/PVC on the effect of copper loadings (10wt%, 20wt% and 30wt%) on TiO2. The characteristic of the photocatalyst was analysed by X-ray diffraction (XRD).